Interrelationships of Personal Values: A Moderated Mediation Analysis Based on Gender and Age - Romanyuk, Lyudmyla (East European Journal of Psycholinguistics, 2017)
The present study describes ten personal values expressed by men and women from two countries, and it explores the relationships between two opposing values, Achievement and Benevolence, specifying Stimulation as a mediator between them. It is further explored whether such a mediation model could be further qualified by age and Gender as moderators. The 40-item Portraits Values Questionnaire (PVQ), measuring ten basic values, was administered to 1,000 young adults from two countries. Hierarchical regression methods were applied to examine mediation and moderation mechanisms.Minor gender and country differences emerged for some of the ten basic values. An indirect relationship among the three selected values was identified. Stimulation was found to operate as a mediator between achievement and benevolence. A conditional process model was established with Gender moderating the Achievement – Stimulation path (men had a steeper slope than women), whereas age moderated the Stimulation – Benevolence path (younger individuals had a steeper slope than older ones). Gender also moderated the Achievement – Benevolence path (men had a steeper slope than women). For men, the association between achievement and stimulation was stronger than for women. For the younger persons, the association between stimulation and benevolence was stronger than for older ones. For women, the level of benevolence was independent of their achievement level. The present analyses shed new light on indirect and differential associations among personal values, adding a novel perspective to research on cognitive mechanisms involved in the ten basic values’ becoming.ReferencesBardi, A., & Schwartz, S.H. (2003). Values and behaviour: Strength and structure of relations. Personality and Social Psychology Bulletin, 29(10), 1207–1220.Berlyne, D. Conflict, arousal and curiosity. New York: McGraw-Hill. 1960.Burgoyne, C.B. & Lea, S.E.G. (2006). Money is material. Science, 314(5802), 1091–1092.Hayes A. (2013). Introduction to mediation, moderation, and conditional process analysis: a regression-based approach. New York: Guilford Press.Kluckhohn, C. (1951). Values and value-orientations in the theory of action: An exploration in definition and classification. In: Toward a General Theory of Action, (pp. 388-433). T. Parsons & E. Shils (Eds.), Cambridge, MA: Harvard University Press.Korman, A. (1974). The Psychology of Motivation. Englewood Cliffs, NJ: Prentice-Hall.Maio, G. R., Hahn, U., Frost, J., & Cheung, W. (2009). Applying the value of equality unequally: Effects of value instantiations that vary in typicality. Journal of Personality and Social Psychology, 97(4), 598–614.Maio, G.R., Pakizeh, A., Cheung, W.Y. & Rees, K.J. (2009). Changing, priming, and acting on values: effects via motivational relations in a circular model. Journal of Personality and Social Psychology, 97(4), 699–715.Maslow, A.H. (1965). Eupsychian management. Homewood, IL: Dorsey.Parks-Leduc, L., Feldman, G., & Bardi, A. (2015). Personality traits and personal values: A meta-analysis. Personality and Social Psychology Review, 19(1) 3–29.Parsons, T. & Bales, R. F. (1953). Family, Socialization, and Interaction Process. Glencoe: Free Press.Prince-Gibson, E., & Schwartz, S. H. (1998). Value priorities and gender. Social Psychology Quarterly, 61, 49-67.Schwartz, S. H. (1992). Universals in the content and structure of values: Theoretical advances and empirical tests in 20 countries. Advances in Experimental Social Psychology, 25, 1-65.Schwartz, S. H. & Sagiv, L. (2000). Value Priorities and Subjective Well-Being: Direct Relations and Congruity Effects. European Journal of Social Psychology, 30, 177-198.Schwartz, S. H., Melech, G., Lehmann, A., Burgess, S., Harris, M., & Owens, V. (2001). Extending the cross-cultural validity of the theory of basic human values with a different method of measurement. Journal of Cross Cultural Psychology, 32, 519-542.Vohs, K.D., Mead, N.L. & Goode, M.R. (2006). The psychological consequences of money. Science, 314 (5802), 1154–1156.Wade, M.D., Liu, L.A. & Vacek, J. (2011). Values and Upward Influence Strategies in Transition: Evidence From the Czech Republic. Journal of Cross-Cultural Psychology, 42 (2), 288–306.